Isosteres of ester derived glucose uptake inhibitors. Issue 18 (15th September 2020) - Roberts, Dennis A.; Wang, Liyi; Zhang, Weihe; Liu, Yi; Shriwas, Pratik; Qian, Yanrong; Chen, Xiaozhuo; Bergmeier, Stephen C.
Graphical abstract: Abstract: Glucose transporters (GLUTs) facilitate glucose uptake and are overexpressed in most cancer cells. Inhibition of glucose transport has been shown to be an effective method to slow the growth of cancer cells both in vitro and in vivo. We have previously reported on the anticancer activity of an ester derived glucose uptake inhibitor. Due to the hydrolytic instability of the ester linkage we have prepared a series of isosteres of the ester moiety. Of all of the isosteres prepared, the amine linkage showed the most promise. Several additional analogues of the amine-linked compounds were also prepared to improve the overall activity.